Odpowiedź :
Odpowiedź:
a) = x^3 + 6x^2 + 12x^2 + 8 - 2x^2 - 4x= x^3 +16x^2 - 4x + 8
b) = 3p^2 - p^3 + p^3 - 3p^2 + 3p^2 - 1^3= 3p^2 - 1
c) = 15a^2b - a^3 + a^3 - 15a^2b + 15ab^2 - 125b^3 = 15ab^2 - 125b^3
d) = x^3 + 6x^2y + 6xy^2 + 8y^3 - 6x^2y - 6xy^2 = x^3 + 8y^3
e) = p^3 + 9p^2 + 27p + 27 - (p^2 - 4p + 4) = p^3 + 9p^2 + 27p + 27 - p^2 + 4p - 4 = p^3 + 8p^2 + 31p + 23
f) = t^2 + 10t + 25 + t^3 -15t^2 + 75t - 125 = t^3 - 14t^2 + 85t - 100
g) = m^3 + 3m^2 + 3m +1 + m^3 - 3m^2 + 3m -1 = 2m^3 + 6m
h) = x^3 + 3x^2y + 3xy^2 +y^3 + x^3 - 3x^2y + 3xy^2 - y^3 = 2x^3 + 6xy^2
i) = a(a^3 + 3a^b + 3ab^3 + b^3) - b(a^3 - 3a^2b + 3ab^2 - b^3) = a^4 + 3a^3b + 3a^2b^2 + ab^3 - (a^3b - 3a^2b^2 + 3ab^3 - b^4) = a^4 + 3a^3b + 3a^2b^2 + ab^3 - a^3b + 3a^2b^2 - 3ab^3 + b^4 = a^4 + 4a^3b +6a^2b^2 - 2ab^3 - 2ab^3 + b^4